INNOVATIVE FORMS OF COOPERATION WITH PARENTS IN PRESCHOOL EDUCATION (Ustozlar uchun, 2025)
this article examines innovative forms of cooperation with parents in preschool education and highlights their impact on children’s development, educators’ work, and the overall quality of the educational process. The study explores digital communication platforms, interactive learning programs, family-centered projects, and collaborative pedagogical approaches that strengthen partnerships between teachers and parents. Modern strategies aimed at increasing parental engagement and improving early childhood education outcomes are also analyzed.